Muscarinic Activation Enhances the Anti-proliferative Effect of Paclitaxel in Murine Breast Tumor Cells - Javier Español, Alejandro; Jacob, Guillermina; Dmytrenko, Ganna; Elena Sales, Maria (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Muscarinic acetylcholine receptors (mAChR) are expressed in cells without nervous origin. mAChR are up-regulated in tumor cells and their stimulation can modulate tumor growth. In this work we investigated the ability of mAChR activation to induce tumor cell death. We studied the action of a combination of low doses of the muscarinic agonist carbachol plus paclitaxel, a chemotherapeutic agent frequently used in breast cancer treatment, in terms of effectiveness. Long term treatment with carbachol exerted anti-proliferative actions on LM2 and LM3 murine mammary adenocarcinoma cells, similarly to paclitaxel. The combination of carbachol with paclitaxel at submaximal concentrations, added during 20 h decreased tumor cell proliferation in a more potent manner than each drug added separately. This effect was reverted by the muscarinic antagonist atropine, and was due to a potentiation of tumor cell apoptosis tested by TUNEL assay. This treatment did not affect the proliferation of the non tumorigenic mammary cell line NMuMG. In conclusion, the combination of a muscarinic agonist plus paclitaxel should be tested as a useful therapeutic tool in breast cancer treatment.
Keywords: Apoptosis - breast cancer cells - muscarinic receptors - paclitaxel